Complicated intrathoracic tuberculosis: Role of therapeutic interventional bronchoscopy. (March 2023) - Goussard, Pierre; Eber, Ernst; Venkatakrishna, Shyam; Frigati, Lisa; Janson, Jacques; Schubert, Pawel; Andronikou, Savvas
Abstract: In recent years bronchoscopy equipment has been improved with smaller instruments and larger size working channels. This has ensured that bronchoscopy offers both therapeutic and interventional options. As the experience of paediatric interventional pulmonologists continues to grow, more interventions are being performed. There is a scarcity of published evidence in the field of interventional bronchoscopy in paediatrics. This is even more relevant for complicated pulmonary tuberculosis (PTB). Therapeutic interventional bronchoscopy procedures can be used in the management of complicated tuberculosis, including for endoscopic enucleations, closure of fistulas, dilatations of bronchial stenosis and severe haemoptysis. Endoscopic therapeutic procedures in children with complicated TB may prevent thoracotomy. If done carefully these interventional procedures have a low complication rate.